Aesthetic Treatments in Cancer Patients - Proietti I; Skroza N; Mambrin A; Marraffa F; Tolino E; Bernardini N; Marchesiello A; Rossi G; Volpe S; Potenza C (Dove Medical Press, 2021)
Ilaria Proietti,1 Nevena Skroza,1 Alessandra Mambrin,1 Federica Marraffa,2 Ersilia Tolino,1 Nicoletta Bernardini,1 Anna Marchesiello,1 Giovanni Rossi,1 Salvatore Volpe,1 Concetta Potenza1 1Dermatology Unit "Daniele Innocenzi", Department of Medical-Surgical Sciences and Biotechnologies, Sapienza University of Rome, Fiorini Hospital, Polo Pontino, Terracina, 04019, Italy; 2Department of Clinical Internal, Anaesthesiologic and Cardiovascular Sciences, Sapienza University of Rome, Rome, ItalyCorrespondence: Ilaria ProiettiDermatology Unit "Daniele Innocenzi", Department of Medical-Surgical Sciences and Biotechnologies, Sapienza University of Rome, Fiorini Hospital, Polo Pontino, Terracina, 04019, ItalyEmail ilaria.proietti@uniroma1.itAbstract: Cancer patients are experiencing an increase in overall survival as a consequence of earlier diagnosis and newer effective anticancer therapies. However, cancer survivors often face long-term consequences from their original cancer diagnosis and long-term sequelae of anticancer treatment. Maintaining patients' quality of life is of paramount importance and this can be accomplished by a multidisciplinary treatment approach, including aesthetic treatments to improve patients' body image and positively impact their quality of life. In this perspective, we will discuss the importance of aesthetic treatments in cancer patients. In addition, we will summarise the data available regarding the use of several aesthetic treatments such as fillers, botulinum toxin and laser use in cancer patients, their safety, their efficacy, and the specific precautions that need to be implemented in this particular subset of cancer patients.Keywords: aesthetic treatment, cancer patient, fillers, botulinum toxin, laser therapy